2020
DOI: 10.3389/fchem.2020.00688
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Enhancing Poly(Lactic Acid) Stereocomplex Formation for Material Property Improvement

Abstract: The production and utilization of polymers have been widely implemented into diverse applications that benefit modern human society, but one of the most valuable properties of polymers, durability, has posed a long-standing environmental challenge from its inception since plastic waste can lead to significant contamination and remains in landfills and oceans for at least hundreds of years. Poly(lactic acid) (PLA) derived from renewable resources provides a sustainable alternative to traditional polymers due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 79 publications
0
53
0
Order By: Relevance
“…Recently, numerous studies have reported that stereocomplex polylactide (sc-PLA) with improved physical characteristics can be used in drug delivery and as molecular carriers [ 10 , 11 , 12 ]. Nanoparticles, such as microspheres and micelles of sc-PLA, have the advantage of controlling drug uptake and release patterns through their synthesis and modification, as well as natural adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies have reported that stereocomplex polylactide (sc-PLA) with improved physical characteristics can be used in drug delivery and as molecular carriers [ 10 , 11 , 12 ]. Nanoparticles, such as microspheres and micelles of sc-PLA, have the advantage of controlling drug uptake and release patterns through their synthesis and modification, as well as natural adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…As the crystal structure of s-PLA has unique characteristics with higher thermal and mechanical properties, crystalline s-PLA can be utilized as a nucleating agent to improve the thermal and mechanical properties of PLA [8,11]. Many studies have reported strategies to improve the properties of PLA through s-PLA formation [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of s-PLA crystalline with various chain structures in the PLA brings higher mechanical and thermal properties [16]. Property enhancement by s-PLA will affect PLA processing: thermal processing, additive manufacturing, and solution casting [17]. Thermal and mechanical enhancement of PLA through stereocomplexation has been utilized to obtain stable PLA materials which are suitable for many applications, especially use as high-performance materials [8,[14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the mechanical properties of PLA are similar to those of common fossil fuel-based thermoplastics; however, the glass transition temperature (T g ), ductility, and thermal stability are lower. Thus, different types of additives are commonly used to improve the properties of PLA [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%